Jellyfish swarm impair the pretreatment efficiency and membrane performance of seawater reverse osmosis desalination. (15th May 2022) - Rahav, Eyal; Belkin, Natalia; Nnebuo, Oluebube; Sisma-Ventura, Guy; Guy-Haim, Tamar; Sharon-Gojman, Revital; Geisler, Eyal; Bar-Zeev, Edo
Highlights: Jellyfish biodegradation led to feedwater eutrophication and bacterial proliferation. TEP passed the pretreatment stages and reached the RO membranes. Jellyfish led to the development of severe bacterial and organic RO biofouling. RO-TMP has abruptly increased three days after the appearance of jellyfish. Abstract: Circumstantial evidence has suggested that jellyfish swarms impair the operation of seawater reverse osmosis desalination facilities. However, only limited information is currently available on the pretreatment efficiency of jellyfish and their effects on reverse osmosis (RO) membrane performance. Here, we have comprehensively tested the pretreatment efficiency of a dual-media gravity filter and cartridge micro-filtration following the addition of jellyfish into the feedwater. Concurrently, the fouling propensity and performance of the RO membranes were examined. We show that jellyfish demise resulted in seawater eutrophication that triggered a significant increase in bacterial biomass (∼50-fold), activity (∼7-fold), and release of transparent exopolymer particles (∼5-fold), peaking three days after the addition of jellyfish into the feedwater. In parallel, a significant reduction in permeate water flux was recorded (∼10%) while trans-membrane pressure sharply increased (15%), reaching the operation pressure limit of our system (75 bar) after five days. At the conclusion of the experiments, the membrane surface was heavily covered by large chunks of organic-rich material and multilayered biofilms. Our results provide a holistic view on the operational challenges of seawater reverse osmosis (SWRO) desalination triggered by jellyfish swarms in coastal areas. Following the above, it can be inferred that freshwater production will likely be halted three days after drawing the jellyfish into the pretreatment system. Outcomes from these results may lead to the development of science-based operational protocols to cope with growing occurrence of jellyfish swarms around the intake of SWRO desalination facilities worldwide. Graphical abstract: Image, graphical abstract